Immunobiotic Lactobacillus rhamnosus strains differentially modulate antiviral immune response in intestinal epithelial and antigen presenting cells - Villena, Julio Cesar (2014)
Background: previous findings suggested that Lactobacillus rhamnosus CRL1505 is able to increase resistance of children to intestinal viral infections. However, the intestinal cells, cytokines and receptors involved in the immunoregulatory effect of this probiotic strain have not been fully characterized. Objective: we aimed to gain insight into the mechanisms involved in the immunomodulatory effect of the CRL1505 strain and therefore evaluated in vitro the crosstalk between L. rhamnosus CRL1505, porcine intestinal epithelial cells (IECs) and antigen presenting cells (APCs) from swine Peyer?s patches in order to deepen our knowledge about the mechanisms, through which this strain may help preventing viral diarrhoea episodes. Results: L. rhamnosus CRL1505 was able to induce IFN?α and ?β in IECs and improve the production of type I IFNs in response to poly(I:C) challenge independently of Toll-like receptor (TLR)-2 or TLR9 signalling. In addition, the CRL1505 strain induced mRNA expression of IL-6 and TNF-α via TLR2 in IECs. Furthermore, the strain significantly increased surface molecules expression and cytokine production in intestinal APCs. The improved Th1 response induced by L. rhamnosus CRL1505 was triggered by TLR2 signalling and included augmented expression of MHC-II and co-stimulatory molecules and expression of IL-1β, IL-6, and IFN-γ in APCs. IL-10 was also significantly up-regulated by CRL1505 in APCs. Conclusions: it was recently reviewed the emergence of TLR agonists as new ways to transform antiviral treatments by introducing panviral therapeutics with less adverse effects than IFN therapies. The use of L. rhamnosus CRL1505 as modulator of innate immunity and inductor of antiviral type I IFNs, IFN-γ, and regulatory IL-10 clearly offers the potential to overcome this challenge.